PERBEDAAN GOLONGAN PENDUDUK DALAM PROSES PENDAFTARAN HAK ATAS TANAH KARENA PEWARISAN - Andraini, Fitika (Notarius, 2009)
The rights for enrolling the land onwed is an ordinary enrollment activity held by BPN in the effort to guarantee the assurance of law of the land owned. Government rules No.24 year 1997 obliged the society to enroll the passing rights due to inheritaged in order to give law protection to the beneficiary and to make the administration activity in order so that the saved and published data are always up dated. Chapter 111 verse (1) the rules made by Minister of Agraria/Head of BPN No. 3 year 1997 about the action for the government rule no.24/1997 arranges that the application for passing rights of land owned or house owned or apartment is enclosed with the proof of legal beneficiary letter.. Based on this rule, the making of the beneficiary proof is determined by the ethnic, the form as well as the officer who made, is for Indonesian citizen, the letter of beneficiary made by the legal beneficiary is made by the local authorities namely the head of the village (kelurahan) and head of district (camat) when the inheritor died, and for Tionghoa, the certificate for the beneficiary right for the land owned is made by the noctary and for the foreign east ethnic, the certificate is made by the Balai Harta Peninggalan.The Rules above do not match accordingly with some rules that are higher in hierarchy namely UUD 1945, UUPA, UU No.12 year 2006 and UU No.26 year 2006. Those rules do not differ the Indonesian citizen.The way to overcome the obstacle is conducting a survey using yuridiction emphirical methode. The study specification is analytical descriptive in nature, the data are collected through the primary and secondary data and then are analyzed qualitatively.The different citizen is an inheritage from the Dutch Colonial that differs the citizen into three social classes namely foreign east society (Tionghoa and non Tionghoa) and Indonesian natives based on the chapter 131 juncto chapter 163 from IS. The rules caused each social class has their own inheritaged law and made them obey their own law. The inheritaged pluralism law caused the making of the ethnic based inheritaged law. The reorientation for the arrangement of inheritaged law is needed to be unified for the function and purpose.Kata Kunci : Social Classes, Land Enrollment, Inheritaged lawPermalink : http://ejournal.undip.ac.id/index.php/notarius/article/view/1129